High risk US adults with untreated hyperlipidaemia in NHANES: estimated reduction in cardiovascular events with statin treatment. (25th November 2020) - Toth, P.P; Palmer, M.K
Abstract: Introduction: Dyslipidemia is widely prevalent. Despite guidelines that recommend statin therapy for high-risk patients, many of these patents are untreated. This gap in care must be urgently closed. Purpose: We analyzed data from the National Health and Nutrition Examination Survey (NHANES) in order to: (1) ascertain the number of high-risk individuals with dyslipidaemia not receiving lipid lowering therapy in the United States; and (2) estimate the reduction in acute cardiovascular (CV) events if those individuals were treated with either moderate or high potency statins in order to achieve at minimum a 30% or 50% reduction in LDL-C levels. Methods: Data from NHANES participants who had fasting blood serum data available, including lipids, were included in our analysis (n=14, 888). Statistical analyses were performed in the R language. Coronary heart disease (CHD) risk was assessed using NCEP ATP III criteria, and participants were categorized as being at high, intermediate, or low CHD risk. Data from seven surveys from 2003–4 to 2015–6 was used and extrapolations to the US adult population (50 states plus the District of Columbia) were performed using the direct method to the US Census 2000 population. Results: We identified 1162 adults (age 20–79) who were high-risk and untreated despite being hyperlipidaemic (LDLC ≥100mg/dL). We estimated they represent 12.8 million individuals in the US 2015–16 population. Without lipid modification and hypothecating 10-year risks of CV events in this group of 20, 25, 30, 35 and 40%, respectively, predicted numbers of CV events are 2.6M, 3.2M, 3.9M, 4.5M, and 5.1M. Moderate-intensity statins reduce LDLC by 30–40% and high-intensity statins by 50–60%. Using untreated LDL-C values from all NHANES surveys we calculated predicted absolute reductions in LDL-C would be at least 42 mg/dL if a moderate-intensity statin was used and at least 70 mg/dL if a high-intensity statin was used, with reductions in CV risk of at least 27% and 46%, respectively. In this group of untreated high-risk individuals, predicted numbers of CV events that could be prevented by moderate-intensity statin for 10 years range from at least 0.7M to at least 1.4M, and with high-intensity statin use for 10 years from at least 1.2M to at least 2.3M, depending on the level of untreated risk. With Numbers Needed to Treat (NTT) between 5 and 18, use of statin treatment in this group would be highly beneficial and cost-effective. Conclusions: There are a large number of untreated high-risk individuals with dyslipidaemia in the US. Use of moderate and high dose statin therapy in these patients for 10 years would reduce CV risk by at least 27% and 47%, respectively. Among untreated high-risk patients, the NNTs for moderate and high dose statin therapy are 9–18 and 5–11, respectively, depending on 10-year level of CV risk. The quality of life and socioeconomic implications of these estimates are substantial. Funding Acknowledgement: Type of funding source: None